Monitoring recent (2018–2023) glacier and rock glacier changes in Central Patagonia using high-resolution Pléiades and ALOS PRISM satellite data - Falaschi, Daniel; Blöthe, Jan; Berthier, Etienne; Tadono, Takeo; Villalba, Ricardo (Frontiers in Earth Science, 2025)
Glaciers and rock glaciers are essential components of the cryosphere in the Andes of Argentina and Chile, serving as significant freshwater reservoirs and playing a crucial hydrological role as the region experiences warming and drying trends. Although the climate response of glaciers and rock glaciers can be different, studies evaluating simultaneous changes in both glaciers and rock glaciers remain scarce. Here, we analyze glacier geodetic mass balance and rock glacier surface elevation changes in the Monte San Lorenzo in Central Patagonia during 2018–2023, using sub-meter Pléiades digital elevation models (DEMs). Our findings reveal a record glacier mass loss rate (−1.49 m ± 0.16 w.e. a−1), the highest recorded in the past 60 years for this region. Elevation changes in the six studied rock glaciers ranged from slightly negative to moderately positive (+0.27 ± 0.88 m to −0.46 ± 0.81 m), with their distribution patterns suggesting the occurrence of ʿice-debris complexesʾ. Additionally, we present the first (2008–2023) rock glacier kinematic assessment in the Patagonian Andes applying feature-tracking to Pléiades and ALOS PRISM satellite images, and find median velocities ranging between 0.14 m a−1 and 0.43 m a−1. While glaciers in the region showed unprecedented negative mass balance conditions since the mid-20th century -coinciding with rising air temperatures and declining precipitation- rock glacier velocities have remained relatively stable across the two sampled epochs (2008–2018 and 2018–2023). The different response of glaciers and rock glaciers reflects the particular response mechanisms and timing in which each of them couples with the climate.